Seroprevalence of anti-ToxoplasmaIgG among the human population in Indonesia: a systematic review and meta-analysis - Taufik Mulya Perdana; Alfin Harjuno Dwiputro; Stefanie Kusuma; Artha Maressa Theodora Simanjuntak; Frengki Prabowo Saputro Wijayanto (BMC Public Health)
Abstract Background Toxoplasma gondii is a ubiquitous parasite that can cause significant complications when it infects pregnant women and immunocompromised patients. These complications include miscarriage, fetal abnormalities, and fatal cerebral toxoplasmosis. Despite its significance, the true burden of toxoplasmosis in Indonesia remains underexplored. Toxoplasmosis is usually diagnosed by detecting anti-Toxoplasma antibodies, especially IgG. Therefore, we aim to assess the seroprevalence of anti-Toxoplasma IgG among the human population in Indonesia. In addition, we assessed whether the seroprevalence differed across geographical regions, populations, or population risk levels. Its correlation with annual precipitation was also assessed. Methods Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we conducted a systematic review and meta-analysis of data retrieved from PubMed, Portal Garuda, Neliti, and Onesearch.id. Additionally, Google Scholar, government repositories, and the reference list of studies were searched for additional data. We pooled seroprevalence data using the inverse-variance method and a random effects model. Heterogeneity was assessed using I2 statistics and Cochran’s Q test. Risk-of-Bias (RoB) was evaluated using the Joanna Briggs Institute Checklist for Prevalence Studies. Publication bias was assessed using Doi plots and the Luis Furuya-Kanamori (LFK) index. We performed subgroup analysis, meta-regression, and sensitivity analysis to explore source heterogeneity and the robustness of the pooled estimates. We used Spearman's rank correlation coefficient to assess the correlation between seroprevalence and annual precipitation. Result In total, 56 studies were included in this study. The adjusted seroprevalence of anti-Toxoplasma IgG was 60.06% (95% CI: 52.22–67.65%). Study location and detection method were detected as significant sources of heterogeneity by subgroup analysis but not meta-regression. However, subgroup analysis and meta-regression identified the study population and population risk level as significant sources of heterogeneity. Publication year, sample size, and RoB were identified as non-significant moderators. Seroprevalence did not correlate with annual precipitation. Conclusion Toxoplasmosis is highly prevalent among the human population in Indonesia; however, our study mainly relied on studies with small sample sizes. Furthermore, most of the studies were performed in Java; therefore, some high-quality population-based studies must be conducted in other regions of Indonesia to better estimate the prevalence of toxoplasmosis across the country.